Analisis Kebolehan Rumah Tangga Poligami Perspektif Agama Dan Negara - Rico Setyo Nugroho (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Polygamy is a practice that has existed and has been in effect for a long time throughout human civilization carried out by the nation and culture of Manan, including in the state of Indonesia. Indonesia since the pre-independence era has also practiced polygamy. The purpose of this study is to analyze the ability of polygamous household practices. This research includes qualitative research with a literature approach or library research so that it does not require research samples or surveys. The method of data collection using primary data is in the form of Marriage Law No. 1 of 1974 articles 4 and 5, Compilation of Islamic Law (KHI) articles 55 and 59, while secondary data uses various references, both journals, books, and those relevant to the research theme. The result of this study is that the practice of polygamy is one of the role models that is allowed by having to meet the terms and conditions that have been set by the law.